Financial Performance Assessment Using Balanced Scorecard Methodology in Indonesian Banks - Syahputra, Danil; Ningsih, Supiah; Marpaung, Durahman (International Journal of Economics (IJEC), 2024)
The objective of this study is to assess the financial performance of XYZ Bank through the lens of the balanced scorecard approach. The research method employed is qualitative, with data drawn from the annual reports of the banks in question for the period spanning 2020 to 2021. This period encompasses both the pre-merger and post-merger phases of Bank Syariah Indonesia. The findings of this study indicate that, from a financial perspective, the combined ROE ratio of the three Islamic banks, which has undergone a merger, is improving and includes healthy qualifications, approaching 15%. The customer perspective reveals an encouraging improvement in profitability, which is attributable to both customer migration from the predecessor bank to the merged bank and new customer growth. The merger has facilitated operating efficiency due to the synergy of the merger, leading to an increase in employee productivity, as measured by revenue. The establishment of several business unit networks represents an innovative form of internal business process, which can facilitate service delivery. The implications of this research provide a more detailed description of performance measurement using data from the company's published annual reports. Previous balance scorecard research employed survey methods in order to obtain information related to the growth and learning perspectives, as well as the customer and internal business process perspectives. In contrast, this study uses only data from the company's financial statements and annual reports.